Redox proteomics : (Wiley-Interscience, 2006)
The relatively new and rapidly changing field of redox proteomics has the potential to revolutionize how we diagnose disease, assess risks, determine prognoses, and target therapeutic strategies for people with inflammatory and aging-associated diseases. This collection brings together, in one comprehensive volume, a broad array of information and insights into normal and altered physiology, molecular mechanisms of disease states, and new applications of the rapidly evolving techniques of proteomics.